Analisis Sentimen Terhadap Masyarakat Indonesia Di Masa PPKM Menggunakan Algoritma NaÃ¯ve Bayes - Ahmad Turmudi Zy; Aswan S Sunge; Riani Riani; Edy Widodo (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Abstract Coronavirus is a group of viruses that can cause disease in animals or humans. Several types of coronavirus are known to cause respiratory tract infections in humans ranging from coughs and colds to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). One of the topics currently being discussed by the public, including on social media Twitter, is the government's policy regarding the Enforcement of Restrictions on Community Activities (PPKM). PPKM is a policy of the Government of Indonesia to deal with COVID-19 that has been made since early 2021. The implementation of PPKM raises pros and cons from the community. Based on the results of the SRMC survey reported through the saifulmunjani.com page, it was stated that nationally, 44% chose to strictly implement PPKM even though on the other hand income decreased, and 40% chose to stop PPKM with an increased risk of COVID-19 transmission. Based on the problems that occurred, it became the basis of this research which aims to find out how the public sentiment towards the implementation of PPKM policies in Indonesia through tweets and comments on the Twitter social media platform using sentiment analysis Keywords: PPKM, NaÃ¯ve bayes, Covid19